Least-Cost Feed Formulation for Juvenile Macrobrachium rosenbergii (De Man) by Using the Linear Programming Technique - Law, A. T.; Poh, Y. T.; Ang, K. J. (Universiti Putra Malaysia Press, 1993)
Linear least-cost programming was used in juvenile M. rosenbergii feed formulation using locally available feed ingredients (fish meal, shrimp meal, copra meal, soybean meal, wheat flour and palm oil). The following constraints were established: the essential amino acid contents were closely similar to those of juvenile M. rosenbergii, crude fat 5-10% and gross energy 4,400 cal/g with least cost. Four types offeed were produced with protein ranges from 25% to 50%. Growth responses of juvenile M. rosenbergii fed these formulated feeds showed that the 40% protein feed (P40) supported the best specific growth rate and feed conversion ratio. P40 feed is recommended for juvenile M. rosenbergii.